Exploring the Impact of Innovation Activities on Financial Performance in Developed and Emerging Markets - Hee Soo Lee; Nina Shin; Jinho Choi (Systems, 2022)
M&As have been regarded significantly as an alternative entry mode in facilitating firms’ internalization strategy. Limited studies uncover the integrative role of M&As on the firms’ financial performance from various market perspectives. This study explores the relationship between M&As and their financial outcomes from developed and emerging markets. It provides evidence that internalization through M&As has a significant impact on the aggregate market value in both developed and emerging markets, and emerging markets can learn from the varying impact of innovation activities on financial performance in developed markets. This study provides location and time selection strategies for multinational firms seeking cross-border M&As.